2013
DOI: 10.1098/rspb.2012.2955
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic multiplicative population growth predicts and interprets Taylor's power law of fluctuation scaling

Abstract: Taylor's law (TL) asserts that the variance of the density (individuals per area or volume) of a set of comparable populations is a power-law function of the mean density of those populations. Despite the empirical confirmation of TL in hundreds of species, there is little consensus about why TL is so widely observed and how its estimated parameters should be interpreted. Here, we report that the Lewontin-Cohen (henceforth LC) model of stochastic population dynamics, which has been widely discussed and applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…The higher exponent reflects greater heterogeneity from a pure random distribution. When the exponent is higher than 2, it may propose deterministic and exponential growth (Ballantyne, 2005;Cohen et al, 2013). An earlier study about individual trees also found that the scaling exponent did not fall within the proposed range (Cohen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher exponent reflects greater heterogeneity from a pure random distribution. When the exponent is higher than 2, it may propose deterministic and exponential growth (Ballantyne, 2005;Cohen et al, 2013). An earlier study about individual trees also found that the scaling exponent did not fall within the proposed range (Cohen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Taylor"s Law is one of the most widely verified empirical relationships in ecology. It was verified in hundreds of species including trees (Cohen, Xu, & Schuster, 2012;2013). For our study, Taylor"s Law can be expressed in the following way for this study:…”
Section: Methodsmentioning
confidence: 99%
“…Kilpatrick and Ives (20) proposed that interspecific competition could reduce the value of b. Other models that implied TL were the exponential dispersion model (21)(22)(23), models of spatially distributed colonies (24,25), a stochastic version of logistic population dynamics (16), and the Lewontin-Cohen stochastic multiplicative population model (8). The diversity of empirical confirmations suggests that no specific biological, physical, technological, or behavioral mechanism explains all instances of TL.…”
mentioning
confidence: 99%
“…TL has been verified for hundreds of biological species and nonbiological quantities in more than a thousand papers in ecology, epidemiology, biomedical sciences, and other fields (2)(3)(4). Recently, examples of TL were found in bacterial microcosms (5,6), forest trees (7,8), human populations (9), coral reef fish populations (10), and barnacles (11,12). TL has been used practically in the design of sampling plans for the control of insect pests of soybeans (13,14) and cotton (15).…”
mentioning
confidence: 99%
“…One possible approach is a model of stochastic multiplicative population growth that has been shown to predict TL and to provide an interpretation of the parameters of TL (24). In this model, population density changes from one discrete time (e.g., day or year) to the next discrete time as a result of multiplying the earlier population density by a random positive growth factor, which is assumed to be independently and identically distributed in time.…”
Section: Discussionmentioning
confidence: 99%